(untitled) (Journal of Economic Research & Business Administration, 2016)
The main objectives of study is to validate the theoretical foundations of the innovation infrastructure. The concept, elements, form, composition and role of the innovation infrastructure is disclosed, approaches to its understanding of the various scientists is highlighted. The article shows that the innovation infrastructure is a key element of the national innovation system, by which scientific development transfers from the scientific-technical sphere to the market and the manufacturing sector. The article is noted that the emergence of new models and types of innovation have developed new forms of innovation infrastructure, it is shown that these innovations need not primarily a «hard» infrastructure, but «soft», in particular, networking communities, innovation brokers, crowdsourcing, the development of various partnerships that give new functions to traditional types of knowledge and innovation infrastructure.